If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3p + -1)(3p + 1) = 0 Reorder the terms: (-1 + 3p)(3p + 1) = 0 Reorder the terms: (-1 + 3p)(1 + 3p) = 0 Multiply (-1 + 3p) * (1 + 3p) (-1(1 + 3p) + 3p * (1 + 3p)) = 0 ((1 * -1 + 3p * -1) + 3p * (1 + 3p)) = 0 ((-1 + -3p) + 3p * (1 + 3p)) = 0 (-1 + -3p + (1 * 3p + 3p * 3p)) = 0 (-1 + -3p + (3p + 9p2)) = 0 Combine like terms: -3p + 3p = 0 (-1 + 0 + 9p2) = 0 (-1 + 9p2) = 0 Solving -1 + 9p2 = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 9p2 = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 9p2 = 0 + 1 9p2 = 0 + 1 Combine like terms: 0 + 1 = 1 9p2 = 1 Divide each side by '9'. p2 = 0.1111111111 Simplifying p2 = 0.1111111111 Take the square root of each side: p = {-0.333333333, 0.333333333}
| 0.15x-2.1=0.3(x-5) | | 4a-7b=0 | | x^2=-x^2+8 | | 14x-10=17x-19 | | 4/u=8 | | X^22+14x+49=0 | | x+133=32 | | 2(g-f)=10 | | 6t+11=2t-27 | | 8x^2+10xy+3y^2=0 | | 2(g-h)=10 | | 5z-21=2z | | 3a+21=5a-7 | | 5*3.6= | | x^4+8x^2+15x=0 | | -3+z=7 | | 4+10x=5+x | | n+3=72 | | k+(-1)=9 | | c+4=3c | | 6+e*f=30 | | 15y+12=19y | | 15-4x=17-4x | | 4x3/2-5=103 | | 5x+8-x=20+4x | | 0.8x-0.7=8.1 | | 7b-7=6b | | f+34=47 | | v=12 | | 3*5+j=15 | | f-34=37 | | a/2=5/1/2 |